(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
A successful case study of Ayurveda management of Hepatitis B was reported. A 19 year old patient with classical symptoms of hepatitis B assessed subjectively and objectively and meticulously recorded at all stages. Yellow discoloration of eye, urine, nails and tongue, loss of appetite, generalized itching and fatigue was noted. After enhancing digestive capacity, medicated ghee –‘Vyoshadi grta,’ was administered as per Shaman principles in a dose of 10gm twice daily. Mrudu virechana (mild purgation) induced by Trivrth lehya 20gm which resulted in 5 to 6 Vegas (bouts of loose stools). Agni (digestive capacity) has slowly but gradually increased. Diet quantity and quality was rectified as required. Rasayan prescribed in one single dose daily was Draskhavlehya, after patient showed clinically significant clearance of all symptoms. Rasayana and Ahara vihara management was continued until blood serum hepatitis antigen B reported negative. Liver Function Test, HB percent in laboratory registered normalization and clinical confirmation showed significant results. Photographs of urine and eye documented periodically. Blood reports showed radical improvements. Physically, mentally and spiritually patient has reported wellbeing. Patient moved towards Swasthya (complete wellbeing). This case study guaranteed Ayurveda management as quick, safe and effective. Large scale study was required to reconfirm reports and can be initiated on similar principles and practices.